India and the BRICS A Cautious and Limited Engagement. (January 2017) - Kumar, Rajan
This article seeks to explore the core interests of India at the BRICS (Brazil, Russia, India, China and South Africa). It argues that India joined this organization as a part of its broad strategy to engage with all the major powers. It foresaw significant geopolitical and economic dividends from its association with other emerging states in a multilateral forum. New Delhi actively participated in the BRICS summits and has contributed significantly to its agenda setting and institutionalization. The article also shows how the BRICS has departed from the Non-Aligned Movement (NAM) and India's traditional policy towards the Global South. By entering into a privileged club, India seeks to upgrade its rank and status. Finally, the article discusses the way preponderance of China in this organization and its border conflicts with India have impacted the potential of the BRICS.